A case of intractable infectious keratitis and subsequent flap necrosis after laser in situ keratomileusis - Kazutaka Kamiya (Dove Medical Press, 2009)
Kazutaka Kamiya, Masayuki Kasahara, Kimiya ShimizuDepartment of Ophthalmology, University of Kitasato School of Medicine, JapanAbstract: We report on a patient in whom intractable infectious keratitis and subsequent lamellar flap necrosis necessitating flap amputation after laser in situ keratomileusis (LASIK). A 34-year-old woman undergoing LASIK complained of blurred vision and pain in the left eye. The best spectacle-corrected visual acuity was 0.01, and slit-lamp examination showed a marked presence of stromal infiltrates involving the flap and the underlying stroma in that eye. The patient was treated topically with hourly instillation of micronomicin, levofloxacin, and cefmenoxime, together with systemic administration of imipenem, but the left eye developed corneal flap necrosis. We performed surgical debridement of the diseased stroma and excised the lamellar flap. Since nontuberculous mycobacterium was detected on the surgical instruments, we then added oral clarithromycin, and substituted systemic administration of amikacin with that of imipenem. At one month after the flap removal, the visual acuity gradually improved to 0.7, but the stromal opacity of the central cornea and hyperopic shift of +3.0 diopters remained. LASIK can cause intractable keratitis, resulting in significant visual disturbance that presumably results from insufficient antisepsis of the medical instruments used for this surgery, supporting the importance of strict sterilization of these instruments.Keywords: infectious keratitis, flap necrosis, nontuberculous mycobacterium, sterilization, LASIK